Role of Tyrosine Kinase Inhibitor (TKI) in stage IV adenocarcinoma of lung: Early outcome from tertiary cancer hospital. - Tiwari, Manoj; Thakur, Binay; Khatiwada, Sagar; Bhattarai, Sachee (Nepalese Journal of Cancer, 2025)
Background: Adenocarcinoma of lung is the most common type of non-small cell lung cancer. Driver mutation, especially EGFR mutation is not uncommon and tyrosine kinase inhibitor (TKI) is the mainstay treatment for stage IV disease. We aim to evaluate early outcome and progression free survival (PFS) of TKI with stage IV adenocarcinoma in Nepal.Methods: A prospective observational study was carried out in 20 patients with stage IV adenocarcinoma harboring mutations (EGFR, ALK, ROS-1). Clinicodemographic details, molecular status, type of TKI  PFS and survival outcomes were analyzed.Results: A total of 20 patients were included. The mean age was 57.4 years (range 31–76); 60% were female, and 75% were smokers. EGFR exon 19 deletion was the most frequent mutation (70%), followed by exon 21 (25%). Osimertinib was prescribed to 55% of patients, gefitinib to 40%, and crizotinib to 5%. At 2 years, overall survival was 78%, PFS was with a median survival of 14.6 months.Conclusion: TKIs demonstrated promising short-term survival outcomes in stage IV adenocarcinoma lung within the Nepalese population. Continued follow-up and larger cohorts are needed to define long-term outcomes and resistance mechanisms in this setting.